ANALISIS KEBUTUHAN UNTUK MENUMBUHKAN KEMAMPUAN INTERAKSI SOSIAL ANAK ABK MELALUI PROGRAM BK - Lindiani, Kholifah (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
This study is a descriptive qualitative research aimed at exploring the social interaction skills of students with special needs in schools, as well as the role of the Guidance and Counseling (GC) program in fostering those skills. The subjects of the research included school counselors, the principal, the vice principal, students with special needs, their peers, and the parents of those students. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The findings show that the school implements an inclusive education approach by providing a special admission pathway for students with special needs during enrollment and offering them the opportunity to participate in school activities such as art performances and Islamic holiday celebrations. The school counselor plays an active role by providing individualized counseling services tailored to each student's needs, and by maintaining communication with homeroom teachers and parents. The social interaction skills of students with special needs develop gradually through the inclusive and supportive school environment. The guidance and counseling program is not significantly different from that offered to regular students, but it does take into account the individual needs of students with special needs. Collaboration among the counselor, school staff, and parents plays an essential role in supporting the development of the students’ social skills